Kualitas Layanan, Kepuasan Mahasiswa dan Word of Mouth - Nur Budi Setiawan; Sony Prastanto (Universitas Pendidikan Nasional, 2021)
This study aims to determine the effect of service quality on student satisfaction in doing word of mouth for IST AKPRIND students. The type of research used is exploratory research with a quantitative approach. The sample in this study was 186 respondents who were alumni and active students at IST AKPRIND. The sampling technique used purposive random sampling. The data collection method used in this study used an online questionnaire with the google form application, which was distributed through social media. Data analysis in this study used the Structural Equation Method (SEM) to determine the size of the data, Maximum Likelihood was used where the number of samples was between 100 and 200 respondents. The results showed that the variables tangible, reliability, responsiveness, and assurance had a positive effect on satisfaction but not significant on satisfaction, while the empathy variable had a positive and significant effect on satisfaction. For the mediation variable, satisfaction has a positive and significant effect on word of mouth. Based on the results of this study, it is suggested to the management of IST AKPRIND to improve their services by focusing on the empathy dimension so that student satisfaction increases significantly.